"Al-Urof" implementations in section one at the Omani civil law: a comparative study with the Egyptian and the Jordanian civil laws = إعمال العرف في الكتاب األول من قانون المعامالت المدنية العماني االلتزامات والحقوق الشخصية: دراسة مقارنة بالقانون المدني المصري والقانون المدني األردني - Mubarak Issa, Al-Saidi Majid (OCERINT International Organization Center of Academic Research, 2023)
This study aimed to discuss: the implementation of custom in the introductory chapter, and the first book of the Omani Civil Transactions Law, personal obligations and rights, and its comparison with the Egyptian civil law and the Jordanian civil law. The study adopted two approaches: the inductive approach and the descriptive analytical approach. The study concluded many results, perhaps foremost among them: The Omani and Jordanian legislators agreed; If there is no text, the court rules in accordance with the provisions of Islamic jurisprudence, and if it does not exist, then according to the general principles of Islamic law, and if it does not exist, then according to custom. As for the Egyptian legislator, he presented the custom over the provisions of Islamic law. The three laws agreed on: Considering custom as a measure of abuse in the use of the right, as well as implementing custom in deciding on the finality of the contract with regard to the payment of the down payment. The Omani legislator agreed with the Jordanian legislator, if the contracting parties did not agree to specify the period, the judge may specify it according to custom, while the Egyptian legislator neglected to regulate the option of the condition. The Omani legislator agrees with the Jordanian legislator in implementing custom in the implementation of the contract. The Egyptian legislator agreed with them in determining the requirements of the contract, but he also dealt with what is among its requirements in accordance with the law, custom and justice according to the nature of the disposition. The first Omani and Jordanian legislator; The attribution of custom in determining what conditions are attached to contracts.